The G7 Business Cycle in a Globalized World - Kai Carstensen; Leonard Salzmann (Center for Economic Studies and ifo Institute (CESifo), 2016)
Using a factor structural VAR for 14 countries out of the G20 group, we document that output innovations originating outside the G7 account for shares of 10 to almost 25 percent in the business cycle fluctuations of G7 GDP growth. Using auxiliary regressions, we additionally find that these innovations contribute noticeably, relative to G7 output innovations, to short-term fluctuations in important other national G7 variables such as employment, the current account balance, inflation, and inflation volatility, and in global macroeconomic indicators like the oil price, world stock market returns, and exchange rate volatility. The results indicate that in a globalized world spillovers from emerging markets and industrial countries other than the G7 play a relevant role for major aspects of the G7 and world business cycle.
Keywords: 330; G7; international business cycle transmission; factor structural VAR